From science to arts, IDNLearn.com has the answers to all your questions. Our community provides timely and precise responses to help you understand and solve any issue you face.

Perform the indicated operation & simplify. Express the answer as a complex number. ( 6 − 7 i ) ( − 8 + 3 i ) =___
show your work


Sagot :

( 6 − 7 i ) ( − 8 + 3 i )

First FOIL:

( 6 − 7 i ) ( − 8 + 3 i )  = -48 + 18i + 56i -21i^2

Combine like terms

                                 = -48 + 74i -21i^2

Convert i^2 = -1

                                 = -48 + 74i -21(-1)

And simplify

                                 = -48 + 74i + 21

                                 = -27 + 74i